Math, asked by shrutipaliwal17, 10 months ago

differentiate the following w.r.t x (1+sin^2x)^2 + (1+cos^2x)^3

Answers

Answered by ItSdHrUvSiNgH
0

Step-by-step explanation:

let us suppose,

f(x) =  {(1 +  { \sin}^{2}(x) )}^{2}  +  {(1 + { \cos}^{2} (x) )}^{3}  \\  \\ f'(x) =  \frac{d(f(x))}{dx}  =(2) (1 +  { \sin }^{2} (x))(2)( \cos(x) ) + 3({1 +  { \cos}^{2} (x) )}^{2} (2)( -  \sin(x) ) \\  \\ simplyfying \:  \: this.... \\  \\ f'(x) = 4 \cos(x)  + 4 { \sin}^{2} (x) \cos(x)  - 6 \sin(x)  {(1 +  { \cos }^{2}(x) )}^{2}  \\  \\ f'(x) = 4 { \sin }^{3} (x) \cos(x)  -  \sin(2x)  - 12 { \cos}^{3} (x) \sin(x) - 6 { \cos }^{5}  (x)  \sin(x)

Answered by ItzDinu
2

\huge{\textbf{\textsf{{\color{navy}{An}}{\purple{sw}}{\pink{er}} {\color{pink}{:}}}}}

y = (1 + sin²(x))² + (1 + cos² (x)) ³

So; The first derivative can be given as:

= (1 + sin²x)² + (1 + cos²x)³

Let;

n = 1 + sin²x and u = 1 + cos²x

d dn (n)². d (1 + sin²x) + du (u)³. (1+ cos²x)

dy2(1+ sin²x). (2) (cos(x)) + 3(1 + cos²x)2(2)(-sina)

dy 4cosx+4sin2x.cosæ 6sinx.(1 + cos²x) ²

dy 4 sin ³(x) cos(x) = sin(2x) - = 12cos³ (x) sin(x) - 6 cos ³ (x) sin(x)

  • I Hope it's Helpful My Friend.

Similar questions